Pengadaan Bahan Pustaka di Perpustakaan Politeknik Pertanian Universitas Andalas Payakumbuh - Gusnimar, Gusnimar; Delman, Delman (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2012)
The purpose of this study was: (1) describe the source of procurement of library materials in the Library of the Polytechnic of Agriculture Unand Payakumbuh, (2) describing the obstacles encountered Unand Payakumbuh Agricultural Polytechnic Library in the procurement of library materials and solutions. Sources of data were collected through direct interviews with librarians. The study's findings (1) Source of procurement of library materials in the Library of the Polytechnic University of Agriculture Andalas Payakumbuh of purchases and donations and graduate students of Higher Education, (2) the procurement of library materials library Unand Agricultural Polytechnic Payakumbuh not running properly visible from the lack of budgetary funds for the procurement of materials libraries, lack of attention led to the procurement of library materials, collection of old releases available.Keywords: acquisition; collection development